Opioid-related risk perceptions in chronic pain: influence of patient gender and previous misuse behaviors. Issue 4 (16th April 2022) - Grant, Alexis D.; Miller, Megan M.; Anastas, Tracy M.; Quinn, Patrick; Lok, Benjamin; Hirsh, Adam T.
Abstract : Virtual patient gender and previous opioid misuse behavior had unique and interactive effects on provider perceptions of patient risk for future prescription opioid–related problems. Abstract: Little is known about the factors that influence providers' perceptions of patient risk for aberrant opioid use. Patient gender may interact with previous opioid misuse to influence these perceptions. We asked 131 physicians to view videos and vignettes for 8 virtual patients with chronic pain. Gender (male/female) and previous prescription opioid misuse (present/absent) varied across patients; the vignettes were otherwise balanced on demographic and clinical characteristics. For each patient, providers assessed 4 risk domains: opioid-related adverse events, opioid misuse or abuse, opioid addiction, and opioid diversion. Results indicated a significant gender-by-misuse interaction for risk of opioid misuse or abuse . When previous misuse behaviors were absent, providers rated men at higher risk; there was no gender difference when previous misuse behaviors were present. A significant gender-by-misuse interaction was found for risk of opioid-related adverse events . Providers perceived men to be at higher risk when previous misuse behaviors were absent; there was no gender difference when previous misuse behaviors were present. A significant gender-by-misuse interaction was found for risk of opioid addiction . Providers rated women at higher risk when previous misuse behaviors were present and men at higher risk when previous misuse behaviors were absent. There were significant main effects of gender and misuse for risk of opioid diversion . Providers rated men and those with previous misuse behaviors at higher risk. These results demonstrate that patient gender and previous opioid misuse have unique and interactive effects on provider perceptions of prescription opioid–related risks. Studies are needed to identify the mechanisms underlying these effects, such as gender-based stereotypes about risk-taking and drug abuse.